2015
DOI: 10.1128/aem.01852-15
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria in Durum Wheat Flour Are Endophytic Components of the Plant during Its Entire Life Cycle

Abstract: bThis study aimed at assessing the dynamics of lactic acid bacteria and other Firmicutes associated with durum wheat organs and processed products. 16S rRNA gene-based high-throughput sequencing showed that Lactobacillus, Streptococcus, Enterococcus, and Lactococcus were the main epiphytic and endophytic genera among lactic acid bacteria. Bacillus, Exiguobacterium, Paenibacillus, and Staphylococcus completed the picture of the core genus microbiome. The relative abundance of each lactic acid bacterium genus wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 56 publications
4
67
0
Order By: Relevance
“…High TTA values reflect high concentrations of lactic acid and acetic acid, thanks to a high buffer capacity of teff flour due to its high ash content, and hence the dominance of mainly heterofermentative LAB species; in turn, they imply high acid tolerance of the dominating LAB and yeast species (Van Kerrebroeck et al., ). Furthermore, batch variations in dominating LAB and yeast species are common during sourdough productions and reflect not only the impact of isolation and identification procedures but also the quality of the flour in terms of age, microbial load, stability, etc ., as well as environmental contamination (De Vuyst et al., , ; Huys, Daniel, & De Vuyst, ; Minervini et al., ). For instance, under the laboratory conditions applied in the study of Moroni et al.…”
Section: Discussionmentioning
confidence: 99%
“…High TTA values reflect high concentrations of lactic acid and acetic acid, thanks to a high buffer capacity of teff flour due to its high ash content, and hence the dominance of mainly heterofermentative LAB species; in turn, they imply high acid tolerance of the dominating LAB and yeast species (Van Kerrebroeck et al., ). Furthermore, batch variations in dominating LAB and yeast species are common during sourdough productions and reflect not only the impact of isolation and identification procedures but also the quality of the flour in terms of age, microbial load, stability, etc ., as well as environmental contamination (De Vuyst et al., , ; Huys, Daniel, & De Vuyst, ; Minervini et al., ). For instance, under the laboratory conditions applied in the study of Moroni et al.…”
Section: Discussionmentioning
confidence: 99%
“…Berghofer et al (2003) stated that, although the microorganisms that contaminate cereals are more concentrated in the outer layers of kernels and the flour should theoretically contain a lower bacterial load than caryopses, the conditioning phase before milling can increase flour's microbial content. Furthermore, Minervini et al (2015) demonstrated that LAB are also endophytic components of wheat plants. Thus, when they are found in semolina, they probably originate from inner layers of kernels.…”
Section: Discussionmentioning
confidence: 99%
“…plantarum were only detected after fermentation. Minervini et al (2015) demonstrated that several LAB, including Lb. plantarum, Lb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minervini and co‐workers reported that Staphylococcus spp. was among the main components of the microbiome in wheat grain.…”
Section: Resultsmentioning
confidence: 99%